1998
DOI: 10.1074/jbc.273.20.11991
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Nuclear Localization and Activity of Tissue Transglutaminase

Abstract: Tissue transglutaminase is a calcium-dependent transamidating enzyme that has been postulated to play a role in the pathology of expanded CAG repeat disorders with polyglutamine expansions expressed within the affected proteins. Because intranuclear inclusions have recently been shown to be a common feature of many of these codon reiteration diseases, the nuclear localization and activity of tissue transglutaminase was examined. Subcellular fractionation of human neuroblastoma SH-SY5Y cells demonstrated that 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
143
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(159 citation statements)
references
References 31 publications
16
143
0
Order By: Relevance
“…Active transglutaminase enzyme attaches its substrate, biotinylated-cadaverine, to the exogenous casein target (Case et al 2003). Consistent with previous studies (Lesort et al 1998), we found significant transglutaminase activity in our nuclear preparations from brain tissue (Fig. 5A) that could be inhibited with cystamine (or GTPγS; data not shown).…”
Section: Transglutaminase May Stabilize the Perc-160 Complexsupporting
confidence: 92%
See 1 more Smart Citation
“…Active transglutaminase enzyme attaches its substrate, biotinylated-cadaverine, to the exogenous casein target (Case et al 2003). Consistent with previous studies (Lesort et al 1998), we found significant transglutaminase activity in our nuclear preparations from brain tissue (Fig. 5A) that could be inhibited with cystamine (or GTPγS; data not shown).…”
Section: Transglutaminase May Stabilize the Perc-160 Complexsupporting
confidence: 92%
“…Moreover, one study looking at the distribution of such immunoreactivity for isopeptide crosslinks in brain found some structures in neuronal nuclei in hippocampus (Maggio et al 2001). That transglutaminase can be active in nuclei in response to calcium has been described (Lesort et al 1998), and transglutaminase associates with importin molecules (Peng et al 1999), indicating a possible regulated nuclear function. To date, though, the only nuclear proteins demonstrated to be modified by transglutaminase in response to physiological stimulation are histones (starfish egg fertilization, (Nunomura et al 2003)).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue TG has been implicated in numerous cellular processes such as wound healing (8), differentiation (9 -11), apoptosis (12,13), and cell survival (14 -16). Further, although tTG is found mostly in the cytosol, it is also present in the nucleus (17,18) and associated with the plasma membrane (19). Since intracellular localization affects protein function by determining what interactions are likely to occur, it is possible that by having access to different substrates in different intracellular pools the multiplicity of tTG effects in different cellular pathways may be due to both its localization and which enzymatic activity of tTG is favored (transamidating or GTP binding/hydrolyzing).…”
mentioning
confidence: 99%
“…To accomplish this goal, HEK293 cells were transiently transfected with wild-type tTG (tTG) or tTG without transamidating activity ([C277S]tTG) that were tagged with a nuclear localization sequence (NLS), or a signal sequence that directed proteins to the plasma membrane (Myr/Pal) or with tTG or [C277S]tTG that lacked any added cellular localization sequences and therefore are predominantly cytosolic (17). Apoptosis was subsequently induced by treatment with thapsigargin, an inhibitor of the Ca 2ϩ -ATPase of endoplasmic reticulum that has been shown to induce apoptosis in different cell models (23)(24)(25).…”
mentioning
confidence: 99%
“…Another cytochemical assay is based on the use of directly or indirectly (e.g., through the biotin-streptavidin link) fluorochrome-labeled natural amines. Amine substrates such as fluoresceinated cadaverine (F-CDV) (12), biotinylated pentyl amine (13), or a derivative of green fluorescent protein (14) become attached in situ to the protein in live cells by TGase 2. None of these assays has been adapted to cytometry.…”
mentioning
confidence: 99%